Computer safety, reliability, and security : 35th International Conference, SAFECOMP 2016, Trondheim, Norway, September 21-23, 2016, Proceedings /: 35th International Conference, SAFECOMP 2016, Trondheim, Norway, September 21-23, 2016, Proceedings. (2016) - Unknown
No abstract available